Calcium supplementation, osteoporosis and cardiovascular disease (Swiss Medical Weekly, 2011)
Adequate intakes of calcium and vitamin D are essential preventive strategies and essential parts of any therapeutic regimen for osteoporosis. However, calcium supplementation is not without controversy and benefits on skeletal health need to be balanced against potential risks on cardiovascular disease. The published data so far suggest a potential detrimental effect of calcium supplement on cardiovascular health (i.e. myocardial infarction) although further prospective studies are needed to clarify the gradient of risk. Since food sources of calcium produce similar benefits on bone density as supplements and dietary calcium intake does not seem to be related with adverse cardiovascular effects, calcium intake from nutritional sources needs to be enforced. In patients with low calcium intake supplements are warranted aiming for a total calcium intake of 800 to 1000 mg/d together with adequate vitamin D replacement. Nevertheless we should keep in mind that for significant reduction in fracture risk, pharmacological treatment is mandatory in patients at risk of fractures irrespective of calcium and vitamin D supplementation.